Adoption of P model of communication on the reduction of unemployment in Kaduna State - Ibrahim, Auwal Ahmed; Joseph, Ayodele Babatunde (Journal of Commerce, Management, and Tourism Studies, 2023)
Unemployment is to the time when one is unable to find work. It is retrogressive to development, as it causes setback for national development and growth. This study attempts to look at the dangers of unemployment in Kaduna state and find ways to reduce. It seeks to investigate the dangers of unemployment in Kaduna state. Anchored on the Hypodermic Needle theory, 50 employed and 50 unemployed people within Kaduna using Kaduna South Local Government were purposely selected to be interviewed. The study concludes that for any state or country to develop meaningfully it must have less unemployment rate. It therefore recommended that government should design communication programs on various media to sensitize and enlighten Kaduna state citizens the importance of employment to curtail it.